Trigeminal Nerve Compression Without Trigeminal Neuralgia: Intraoperative vs Imaging Evidence. Issue 1 (6th February 2018) - Jani, Ronak H; Hughes, Marion A; Gold, Michael S; Branstetter, Barton F; Ligus, Zachary E; Sekula, Raymond F
Abstract: BACKGROUND: While high-resolution imaging is increasingly used in guiding decisions about surgical interventions for the treatment of trigeminal neuralgia, direct assessment of the extent of vascular contact of the trigeminal nerve is still considered the gold standard for the determination of whether nerve decompression is warranted. OBJECTIVE: To compare intraoperative and magnetic resonance imaging (MRI) findings of the prevalence and severity of vascular compression of the trigeminal nerve in patients without classical trigeminal neuralgia. METHODS: We prospectively recruited 27 patients without facial pain who were undergoing microvascular decompression for hemifacial spasm and had undergone high-resolution preoperative MRI. Neurovascular contact/compression (NVC/C) by artery or vein was assessed both intraoperatively and by MRI, and was stratified into 3 types: simple contact, compression (indentation of the surface of the nerve), and deformity (deviation or distortion of the nerve). RESULTS: Intraoperative evidence of NVC/C was detected in 23 patients. MRI evidence of NVC/C was detected in 18 patients, all of whom had intraoperative evidence of NVC/C. Thus, there were 5, or 28% more patients in whom NVC/C was detected intraoperatively than with MRI (Kappa = 0.52); contact was observed in 4 of these patients and compression in 1 patient. In patients where NVC/C was observed by both methods, there was agreement regarding the severity of contact/compression in 83% (15/18) of patients (Kappa = 0.47). No patients exhibited deformity of the nerve by imaging or intraoperatively. CONCLUSION: There was moderate agreement between imaging and operative findings with respect to both the presence and severity of NVC/C.